Republic of Lithuania : Second Review Under the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Lithuania showed progress in macroeconomic stability and structural reforms, under the Stand-By Arrangement. Executive Directors welcomed this development, and endorsed the authorities' intention to switch the peg of the litas to the euro, with a view to move toward greater economic integration with the European Union area, while preserving the credibility of the currency board. They welcomed the comprehensive medium-term fiscal framework, which aimed to determine the priorities, address future expenditure pressures, and achieve the medium-term goal of a cyclically balanced budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet